A case-control study to evaluate salivary cortisol levels in patients with dry mouth - Vandana Shekar; Ravi David Austin; Phillips Mathew (Wolters Kluwer Medknow Publications, 2014)
Objective: The purpose of this study is to evaluate the salivary cortisol levels in patients with dry mouth. Materials and Methods: The study population consisted of 20 patients with a complaint of dry mouth and 20 asymptomatic age- and sex-matched controls. In patients who complained of dry mouth, the salivary flow rate (ml/minute) was estimated by measuring the quantity of the saliva collected in the collector. The concentration of cortisol in the saliva (΅g/dl) was determined by using a salivary enzyme-linked immunoassay (ELISA) kit. Statistical Analysis: The results were evaluated using the Student's t-test. Results: There was only a mild increase in salivary cortisol in both stimulated and unstimulated saliva in patients with dry mouth compared to the controls (p-value 0.981 and 0.481, respectively), which was not statistically significant. Conclusion: There may not be a clear association between the salivary cortisol level and dry mouth. In older individuals, age-associated salivary gland hypofunction and life changes may be the main risk factors for dry mouth compared to stress and anxiety.